Reversing the slow death of the clinical necropsy: developing the post of the Pathology Liaison Nurse - Limacher, Eileen (BMJ Group, 2007)
The adult clinical necropsy has been declining for many years and is nearing extinction in many hospitals. In Norwich, to prevent this from occurring, a Pathology Liaison Nurse (PLN) was appointed, resulting in a modest reversal of the trend. In 2005, the number of adult clinical necropsies increased to 58 (clinical necropsy rate = 2.4%) from its nadir of 34 (clinical necropsy rate = 1.4%) in 2003. Moreover, consent is now much more likely to be full and to allow histopathological and other studies. The PLN ensures that consent is properly and fully obtained, in line with current legislation. She also plays an important role in arranging for feedback to be given by clinicians to the families after the examination, and in teaching and training Trust staff about death, bereavement, and related matters. This paper describes how the role of PLN was established and evaluated, and gives details of the current state of the adult clinical necropsy in Norwich.